Toward a notation for modeling value driver trees: Classification development and research agenda - Benjamin Matthies (Journal of Corporate Accounting & Finance, 2024)
Value driver trees (VDTs) are abstract, indicator-based representations of a business model. Although they are conceptual models by nature, no systematic and unified approaches to their modeling exist to date. In fact, a heterogeneous understanding of their conception and methodological implementation has been established. The goal of this study is to provide more clarity in this regard by examining the semantics (the question of "what?") and syntax (the question of "how?") with respect to VDT modeling. For this purpose, a structured literature review was conducted in which a collection of 161 VDTs was evaluated. Based on an extended taxonomy design process, the typical model constructs of VDTs were extracted. As a result, a so-called VDT Model Classification was derived, which structures 34 model constructs into three dimensions with eight categories. This classification establishes a clearer understanding of the model constructs and their representation, thereby providing a conceptual framework for a unified and more substantiated "vocabulary" for VDT modeling. Finally, a research agenda has been formulated that generally addresses the role and future application potential of VDTs and, in particular, describes the next steps toward a sound notation for modeling VDTs.
Keywords: 650; classification; conceptual modeling; literature review; value driver tree; value-based management; visual notation